LINGUISTIC MEANS OF REPRESENTING THE FAMILY PARADIGM IN RUSSIAN AND UZBEK PAREMICS: A COMPARATIVE ANALYSIS - Fatkhullahodjaev Makhmud Zikrullaevich (Social science and innovation, 2024)
This academic article presents a comparative analysis of the linguistic means used in Russian and Uzbek paremics to represent the family paradigm. Drawing upon cultural and linguistic perspectives, the study explores how these languages reflect cultural values, norms, and social structures related to family relationships. Through an examination of linguistic expressions, honorifics, kinship terms, and proverbs, this article sheds light on the ways in which Russian and Uzbek paremics depict familial bonds, hierarchy, collectivism, and the extended family network. The findings highlight the cultural specificity embedded in linguistic representations of the family paradigm and contribute to our understanding of intercultural communication and cultural diversity.